Pencemaran Nama Baik dalam Perspektif Hadits At-Tirmidzi No. 1894 dan Pasal 27A UU ITE - Salwa Muzdalifah; Tajul Arifin (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The crime of defamation in the digital era has become an increasingly complex phenomenon along with the rapid development of information technology. This study aims to analyze the problem of criminal defamation from the perspective of Hadith At-Tirmidzi Number 1894 and Article 27A of the ITE Law. The main focus of the study is on the dynamics of criminal defamation in the context of information and media ethics, the role of hoax news that contributes to the rampant criminal defamation cases, and legal analysis related to both sources. The method used in this study is a qualitative approach with normative analysis of Islamic legal doctrine and positive legal provisions. The results of the study show that Hadith At-Tirmidzi Number 1894 emphasizes the importance of honesty and prohibits lying as part of moral ethics in Islam. Meanwhile, Article 27A of the ITE Law acts as a legal instrument to address criminal defamation violations in the digital realm. A comparison of these two sources shows that although Islamic law and positive law have similarities in maintaining individual honor, the resolution mechanisms are different. Therefore, this study recommends preventive measures such as increasing digital literacy and legal education to reduce the risk of defamation and increase public awareness of the ethics of communicating in cyberspace